Ad-Dirāsah At-Tahlīliyyah Lil Manhaji Ad-Dirāsī Fī Al-Marhalati At-Tsānawiyyati Al- ‘Ammah ‘Alā Asāsi Al-Ithāri Al-Marja’ī Al-Urūbī Al-Musytarakī - Mulyadi Abdullah; Imam Asrori; Abdul Wahab Rosyid (Rayah Al-Islam, 2022)
إن اللغة العربية مفتاح لفهم كتاب الله سبحانه، ونزول القرآن بها أعظم فخر لها وتشريف لها، واللغة العربية قد دخلت في إندونيسيا مع دخول الإسلام فيها في القرن الأول الهجري، فأصبحت اللغة العربية تدرس في المؤسسات التعليمية، أو الجامعات، أو المعاهد الإسلامية وحتى المدارس العامة، ومنها في المدرسة الثانوية العامة، وتهدف هذه الدراسة إلى معرفة الكفاءات الأساسية المطلوبة في المنهج الدراسي لتعليم اللغة العربية في المدرسة الثانوية العامة، وصف مدى تناسب الكفاءات الأساسية في المنهج الدراسي لتعليم اللغة العربية في المدرسة الثانوية العامة، بالمعايير المنصوصة في (الإطار المرجعي الأروبي المشترك)، وسلك الباحث في هذه الدراسة منهج الوصف التحليلي، وأما نتائج هذه الدراسة فهي: وبعد أن تم التحليل للكفاءات الأساسية لتعليم اللغة العربية في الفصل العاشر على أساس الإطار المرجعي الأروبي المشترك تبين أن الكفاءات المطلوبة في ذاك الفصل يبدأ من كفاءة A1ثم،A2 ، ثم c1، ولم تطلب كفاءة B1 وB2 مباشرة إلى كفاءة .C1 والكفاءات المطلوبة في فصل الحادي عشر : A1،A2 ،B1 ، B2، ولم تصل إلى كفاءة C1، ولكن تبدأ من B1 ثم B2، ثم تنزل إلى A1، ثم ترتقي مرة أخرى إلى B1، ثم تنزل مرة أخرى إلى A1، ثم B1، ثم A2. والكفاءات المطلوبة في فصل الثاني عشر:A1، وB1، إلا أنها تبدأ ب B1، ثم تنزل إلى A1. إن الكفاءات في اللغة العربية المطلوبة في المنهج الدراسي في المدرسة الثانوية العامة لا تتوازن مع المستويات الموجودة في الإطار المرجعي الأوروبي المشترك. Arabic is the key to understanding the Book of Allah Almighty, and the revelation of the Qur'an with it is: the greatest pride and honor for him. Arabic has entered Indonesia with the entry of Islam in the first century Hijri, so Arabic began to be taught in educational institutions, universities, Islamic institutions and even public schools. and This study aims to determine the basic competencies required in the Arabic language teaching curriculum in public secondary schools, and to describe the extent to which these basic competencies are appropriate in the Arabic language teaching curriculum in public secondary schools, in accordance with the criteria set out in the Common European Framework of Reference), and the researcher used a descriptive analytical approach in this study, and the results of this study are: After analyzing the basic competencies of teaching Arabic in tenth grade based on the general European frame of reference, it was found that the competencies required for the class started from competence A1, then A2, then C1, and competence B1 and competence B2 were not required, but directly to competency C1, and the competencies required in class eleven are: A1, A2, B1, B2, and not up to competency C1, but starting from B1 then B2, then down to A1, then up again to B1, then down again to A1, then B1, then A2. And the competencies required in the twelfth grade are: A1 and B1, but start from B1, then work their way down to A1, and the competence in Arabic required in the general secondary school curriculum is not commensurate with the levels found in the Common European Terms of Reference.